0.3-V 36-nW Voltage-Mode First-Order Filter Based on Multiple-Input Operational Transconductance Amplifier - Montree Kumngern; Tomasz Kulej; Fabian Khateb (IEEE Access)
This paper presents an electronically tunable, voltage-mode first-order filter based on multiple-input operational transconductance amplifiers (MI-OTAs). The filter circuit consists of two MI-OTAs and a single capacitor. It is demonstrated that a single topology can realize first-order low-pass, high-pass, and all-pass filters using MI-OTA-based designs. These filter responses are achieved without the need for component matching, input matching, or inverting input signals. The pole frequency of all filter responses can be electronically tuned by adjusting the transconductance of the OTA. The MI-OTA operates at 0.3 V with a rail-to-rail input voltage range, thanks to the use of bulk-driven MOS transistors operating in the subthreshold region and the multiple-input MOS transistor technique. This results in a simple CMOS structure with low supply voltage and reduced power consumption. The circuit was designed and evaluated in Cadence Virtuoso using UMC’s 130-nm 1P8M CMOS process. The proposed filter demonstrates improved performance in terms of lower supply voltage and reduced power consumption compared to previous works. It achieves a dynamic range of 52 dB while consuming only 36 nW of power, with a bias current setting of 10 nA.